New records of the eumenine wasps (Hymenoptera: Vespidae: Eumeninae) from Azerbaijan, with description of hitherto unknown male of Ancistrocerus terekensis Kostylev, 1940 and female of Eustenancistrocerus iranicus Gusenleitner, 2013 - Fateryga, Alexander V.; Proshchalykin, Maxim Yu.; Maharramov, Mahir M. (Zootaxa, 2025)
New records of 14 species of the subfamily Eumeninae from the Nakhchivan Autonomous Republic of Azerbaijan are reported, nine of them are new to Azerbaijan: Ancistrocerus nigricornis (Curtis, 1826), A. tenellus (Kostylev, 1935), A. terekensis Kostylev, 1940, Euodynerus fastidiosus de Saussure, 1853, Eustenancistrocerus iranicus Gusenleitner, 2013, Ichnogasteroides picteti tenuis (Morawitz, 1888), Leptochilus neutralis (Giordani Soika, 1943), Microdynerus exilis Herrich-Schäffer, 1839, and Xanthodynerus caucasicus Giordani Soika, 1960. Hitherto unknown male of Ancistrocerus terekensis and female of Eustenancistrocerus iranicus are described. Ancistrocerus scoticus (Curtis, 1826) is excluded from the fauna of Azerbaijan. The number of species of the eumenine wasps in the broad sense known from Azerbaijan is increased to 113.